Long Term Rice-Rape Seed Cropping Effects on Weed Seed Bank Size and Composition - Badshah, M A; Ibrahim, M; Mei, T N (Bangladesh Rice Journal, 2023)
To study the long term rice-rape cropping effect on weed seed bank size and composition, soil samples were collected from a long term (2004–2012) experiment under the cultivation techniques of conventional tillage transplanting (CTTP), no-tillage transplanting (NTTP), conventional tillage direct seeding (CTDS), and no-tillage direct seeding (NTDS) at a various soil depths of 0-5 cm, 5-10 cm, 10-15 cm, and 15-20 cm during 2011- 2012. Results indicated that, the highest weed seed accumulation of most species was in the 0-5 cm soil depth. More than 60% (% to total weed seeds) seeds were germinated at 20 days after placement of tray (DAP). The seed bank size of Echinochloa crus-galli(L) under direct seeded was 53% higher than transplanted in both years irrespective of tillage system. It decreased 67% under CT and 87% under NT from 0-5 to 5-10 cm soil depth in 2011. The ranked of weed species were grass > broad leaf > sedge based on their number per unit area in both years. The rank of Echinochloa crus-galli(L) was CTDS > NTTDS > NTTP > CTTP among the treatments at 0-5 cm soil depth in both years. Monochoria vaginalis (Burm.f) Kunth, Fimbristylis miliacea and C. iria L were fewer in number. The pressure of germination of weed seeds was more at 20 DAP at 0-5 cm soil depth. Total number (up to 60 DAP) of Echinochloa crus-galli was higher in CTDS at 0-5 cm soil depth in both the years and drastically reduced under no tillage than under conventional tillage towards deeper horizon of soil. Bangladesh Rice J. 26 (2): 73-82, 2022